TV Media Change in the Aspect of Remediation Theory - Pečiulis, Žygintas (Information & Media, 2021)
The emergence of TV in the first half of the 20th century became one of the media for mass audiovisual communication, technologically extending the tradition of electric telegraph and radio. Initially, TV was considered a media for transmitting current  processes. With the introduction of video technology in the 1960s, TV began to capture live content and re-display videos. TV content production technologies have been radically changed by video editing, which has brought TV closer to the cinema. Technological changes in the analog era have had a greater impact on content production processes, and the digital era  sparked a revolution in content consumption. Technological changes in the pre-digital and digital era can be seen as progress, but at the same time raises the question of media perception, even survival, as the technologies of production and distribution of TV content and audience behavior change from time to time.
Keywords: media; TV; analog era; digital era; remediation; changes